2016
DOI: 10.1186/s12934-016-0454-2
|View full text |Cite
|
Sign up to set email alerts
|

Medium chain length polyhydroxyalkanoates consisting primarily of unsaturated 3-hydroxy-5-cis-dodecanoate synthesized by newly isolated bacteria using crude glycerol

Abstract: BackgroundOur study aimed to search for novel bacteria capable of producing polyhydroxyalkanoates (PHAs) using crude glycerol residue obtained from biodiesel production in which used cooking oils were the substrates.ResultsNewly isolated bacteria from soils in Thailand were screened for the efficient production of PHAs from crude glycerol. The bacterial strains were cultivated on glucose, refined glycerol, crude glycerol, or various cooking oils (canola oil, palm oil, soybean oil, sunflower oil, corn oil, grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Medium-chain-length PHAs (mcl-PHAs) that contain 6-14 carbon atoms in their monomeric units, are produced by Pseudomonas strains. It has been previously reported that these bacteria can biosynthesize saturated and unsaturated monomers, which in combination with long chains, leads to highly amorphous polymers [2][3][4] . Moreover, there are several studies that demonstrate the biocompatibility of these polymers [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…Medium-chain-length PHAs (mcl-PHAs) that contain 6-14 carbon atoms in their monomeric units, are produced by Pseudomonas strains. It has been previously reported that these bacteria can biosynthesize saturated and unsaturated monomers, which in combination with long chains, leads to highly amorphous polymers [2][3][4] . Moreover, there are several studies that demonstrate the biocompatibility of these polymers [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…and bacteria in the families Rhodocyclaceae, Comamonadaceae, Xanthobacteraceae, Enterobacteriaceae, and Bradyrhizobiaceae have been reported to accumulate PHA. [30][31][32][33][34] All of these groups of microorganisms belong to proteobacteria in the class alphaproteobacteria, betaproteobacteria, or gammaproteobacteria.…”
Section: Microbial Community Analysis Using 16s Rrna Gene Amplicon Sementioning
confidence: 99%
“…For the cell samples, the NMR sample solutions were sonicated for 4 h. The COSY, HSQC and HMBC experiments were carried out with standard Bruker sequences "cosyetgp", "hsqcetgpsisp2.2" and "hmbccgpndqf" respectively, with a scan number of 16 for COSY and of 96 for HSQC and HMBC. All the NMR spectra were analysed with the software Mestrenova (version of 12.0.2) [83].…”
Section: Extraction and Characterization Of Phamentioning
confidence: 99%